Photo/Electrocatalytic Properties of Nanocrystalline ZnO and La–Doped ZnO: Combined DFT Fundamental Semiconducting Properties and Experimental Study. Issue 27 (18th July 2018) - Ahsaine, Hassan Ait; Slassi, Amine; Naciri, Yassin; Chennah, Ahmed; Jaramillo‐Páez, Cesar; Anfar, Zakaria; Zbair, Mohamed; Benlhachemi, Abdeljalil; Navío, Jose Antonio
Abstract: This work reports the synthesis of nanocrystalline ZnO and 5% La‐doped ZnO (La/ZnO) materials for photo/electrocatalytic degradation of Rhodamine B. The samples were characterized by X‐Ray diffraction, scanning and transmission electron microscopy, X‐Ray photoelectron spectroscopy and diffuse reflectance spectra. The effect of La doping on electronic structure was investigated using density functional theory calculations (DFT), La‐doped ZnO showed an n‐type metallic nature compared to pristine ZnO and La doping creates occupied states within the band gap edge. Under UV light, La/ZnO showed higher kinetic constant and efficiency than ZnO. A possible mechanism was elaborated on the basis of DFT and active trapping measurements. Different initial Rhodamine B concentration were studied to assess the electro‐oxidation of RhB. The electrochemical degradation of RhB over La/ZnO spindles electrode was pronounced with three time's high kinetic constant. The superior electro/photoactivity of La/ZnO was due to its unique morphology, high charge separation of the charge carriers and higher conductivity induced by La‐doping (intermediary levels). Superoxide ions and holes were the main active species for the photodegradation. Whereas, synergetic effect of hydroxyl radicals and hypochlorite ions were responsible of the high RhB electrocatalytic degradation. Abstract : This work reports the synthesis of nanocrystalline ZnO and La‐doped ZnO nanopowders for the photocatalytic and electrochemical degradation of RhB. The prepared samples were characterized by different structural and textural techniques. A theoretical DFT study was performed to elucidate the materials behavior and the effect of Lanthanum doping on the catalytic properties.